Influence of TLR-8 Gene Polymorphisms (rs3764880 and rs3788935) Associated to Pulmonary Tuberculosis in Kupang, Indonesia - Charles, Afandi; Penggoam, Simeon; Maskoen, Ani Melani; Sahiratmadja, Edhyana (Indonesian Journal of Tropical and Infectious Disease, 2021)
Toll-like receptor 8 (TLR-8) is known as part of intracellular signaling transduction for bacterial phagocytosis. Mycobacterium tuberculosis (Mtb) is intracellular pathogenic bacteria that is recognized by this receptor, and genetic variation of TLR-8 might alter susceptibility of the host towards pulmonary tuberculosis (PTB). This study aimed to determine whether TLR-8 gene polymorphisms were associated to PTB in Kupang, Indonesia. This case-control study compared demographic and clinical data between 115 PTB patients and 115 controls, then two TLR-8 single nucleotide polymorphisms (rs3764880 and rs3788935) were explored using the GoldenGate® Genotyping for VeraCode® / BeadXpress Illumina®. There is no significant difference between sex distribution of patient vs control groups. The polymorphisms (rs3764880 and rs3788935) are in Hardy-Weinberg Equilibrium in this population (p > 0.05). The distribution of major vs minor genotypes and alleles of TLR-8 polymorphisms in PTB patients were as followed: rs3764880 (GG vs GA vs AA, 50.0% vs 21.4% vs 28.6% ; G vs A, 60.9% vs 39.1% ) and rs3788935 (GG vs GA vs AA, 53.0% vs 21.7% vs 25.3%; G vs A, 62.9% vs 37.1%). Neither genotypes nor alleles were associated with PTB in this population (P > 0.05). Besides, when the analyses were stratified by gender, none of the alleles of polymorphism in both genders were associated with PTB cases. None of the TLR-8 polymorphisms have associated the risk of developing PTB in Kupang, East Nusa Tenggara population (as opposed to other studies in different ethnic groups). These might reflect the diversity of genetic polymorphisms in eastern Indonesia populations, suggesting different genetic backgrounds with western part of Indonesia.